1987
DOI: 10.1016/s0022-5347(17)43119-3
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Ureteropyeloscopy: Diagnosis and Treatment in the Upper Urinary Tract

Abstract: Flexible ureteropyeloscopy was performed on 59 patients with 2.7, 3.2 or 3.6 mm. endoscopes with a deflectable tip. Techniques for use of these flexible endoscopes are discussed in detail. The endoscope could be passed into the ureter in 58 patients and into the kidney in 52 (88 per cent). The entire collecting system was visualized in 23 of the most recent 29 patients (79 per cent). A diagnosis was achieved in all 23 patients with an intrarenal filling defect demonstrated radiographically. The source of gross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(41 citation statements)
references
References 15 publications
0
35
0
1
Order By: Relevance
“…Immediate nephrectomies were performed in 1 of 19 patients with grade 1 carcinoma, 3 of 20 patients with grade 2 carcinoma, 3 of 14 patients with grade 3 carcinoma, and 3 of 30 patients with ungraded carcinoma. Recurrences developed during follow-up in 3 of 18 patients (17%) with grade 1 carcinoma, 4 of 17 patients (24%) with grade 2 carcinoma, 6 of 12 patients (50%) with grade 3 carcinoma, and 7 of 27 patients (26%) with ungraded carcinoma.…”
Section: Resultsmentioning
confidence: 99%
“…Immediate nephrectomies were performed in 1 of 19 patients with grade 1 carcinoma, 3 of 20 patients with grade 2 carcinoma, 3 of 14 patients with grade 3 carcinoma, and 3 of 30 patients with ungraded carcinoma. Recurrences developed during follow-up in 3 of 18 patients (17%) with grade 1 carcinoma, 4 of 17 patients (24%) with grade 2 carcinoma, 6 of 12 patients (50%) with grade 3 carcinoma, and 7 of 27 patients (26%) with ungraded carcinoma.…”
Section: Resultsmentioning
confidence: 99%
“…At the end of 1980s, use of flexible ureteroscopes has gained acceleration with the introduction of devices that have an irrigation channel and a flexible tip (active and passive deflection). Bagley et al [7] published their first fURS study in 1987, thereafter Kavoussi et al [8] reported their series including 76 fURS procedures in 68 patients in 1989. The developments in flexible ureteroscopes in this time have mainly related to decreasing the diameter of the devices and increasing the deflection angles.…”
Section: Historymentioning
confidence: 99%
“…Combined with new technologies for stone comminution (ultrasound, electrohydraulic, pneumatic, laser), electrocautery, and tissue ablation (electrosurgical units, both uni-and bipolar; laser; harmonic scalpel; argon beam; cryoablation; radiofrequency ablation), endourology, the urologic subspecialty of minimally invasive surgery, has experienced an unprecedented rise over the past 25 years [14][15][16][17][18][19][20].…”
Section: Current State-of-the-art In Minimally Invasive Urologic Surgerymentioning
confidence: 99%